Percutaneous retrieval of centrally embolized fragments of central venous access devices or knotted Swan-Ganz catheters. Clinical report of 14 retrievals with detailed angiographic analysis and review of procedural aspects - Kalińczuk, Łukasz; Chmielak, Zbigniew; Dębski, Artur; Kępka, Cezary; Rudziński, Piotr N.; Bujak, Sebastian; Skwarek, Mirosław; Kurowski, Andrzej; Dzielińska, Zofia; Demkow, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction: Totally implantable venous access systems (TIVAS), Swan-Ganz (SG) and central venous catheters (CVC) allow easy and repetitive entry to the central cardiovascular system. Fragments of them may be released inadvertently into the cardiovascular system during their insertion or as a result of mechanical complications encountered during long-term utilization. Aim : To present results of percutaneous retrieval of embolized fragments of central venous devices or knotted SG and review the procedural aspects with a series of detailed angiographies. Material and methods : Between January 2003 and December 2012 there were 14 (~0.025%) successful retrievals in 13 patients (44 ±16 years, 15% females) of embolized fragments of TIVAS (n = 10) or CVC (n = 1) or of dislodged guide-wires (n = 2) or knotted SG (n = 1). Results : Foreign bodies with the forward end located in the right ventricle (RV), as well as those found in the pulmonary artery (PA), often required repositioning with a pigtail catheter as compared to those catheter fragments which were located in the right atrium (RA) and/or great vein and possessed an accessible free end allowing their direct ensnarement with the loop snare (57.0% (4/7) vs. 66.7% (2/3) vs. 0.0% (0/3); p = 0.074 respectively). Procedure duration was 2–3 times longer among catheters retrieved from the PA than among those with the forward edge located in the RV or RA (30 (18–68) vs. 13.5 (11–37) vs. 8 min (8–13); p = 0.054 respectively). The SG catheter knotted in the vena cava superior (VCS) was encircled with the loop snare introduced transfemorally, subsequently cut at its skin entrance and then pulled down inside the 14 Fr vascular sheath. Conclusions : By using the pigtail catheter and the loop snare, it is feasible to retrieve centrally embolized fragments or knotted central venous access devices.